3d transition metals and oxides within carbon nanotubes by co-pyrolysis of metallocene & camphor: High filling efficiency and self-organized structures. (June 2018) - Kapoor, Aakanksha; Singh, Nitesh; Dey, Arka Bikash; Nigam, A.K.; Bajpai, Ashna
Abstract: We demonstrate that a single zone furnace with a modified synthesis chamber design is sufficient to obtain metal (Fe, Co or Ni) filled carbon nanotubes (CNT) with high filling efficiency and controlled morphology. The samples are synthesized by pyrolysis of metallocenes, a technique that otherwise requires a dual zone furnace . The respective metallocenes in all three cases are sublimed in powder form, a crucial factor for obtaining high filling efficiency. While Fe@CNT is routinely produced using this technique, well-formed Ni@CNT or Co@CNT samples are reported for the first time. This is achieved by sublimation of nickelocene (or cobaltocene) in combination with 'camphor.' Ni or Co@CNT exhibit some of the highest saturation magnetization (Ms ) values, at least an order of magnitude higher than that reported earlier. The results elucidate on why Ni or Co@CNT are relatively difficult to obtain by pyrolyzing powder metallocene alone. A systematic variation of synthesis parameters provides insights for obtaining narrow length and diameter distribution with reduced residue particles outside the filled CNT - factors important for device - related applications. Finally, the utility of this technique is demonstrated by obtaining highly aligned forest of Fe2 O3 @CNT, wherein Fe2 O3 is a functional magnetic oxide relevant to spintronics and battery applications. Graphical abstract: Image